PENGARUH PENGENDALIAN INTERN, KOMPETENSI SUMBER DAYA MANUSIA DAN PEMAHAMAN GOOD GOVERNANCE TERHADAP KINERJA PEMERINTAH DAERAH PADA KABUPATEN MALANG (Studi Kasus Pada Organisasi Perangkat Daerah di Kabupaten Malang) - Lavita Safitri Ramadhany; Dwiyani Sudaryanti; Hariri Hariri (Universitas Islam Malang, 2021)
The purpose of this study was to determine the effect of internal control, competence of human resources and understanding of good governance on the performance of local government in Malang Regency. The case study in this research is the regional apparatus organization in Malang Regency. This study uses purposive sampling technique in determining the sample and obtained as many as 40 respondents. The data analysis technique in this study used multiple linear regression analysis. The results of this study are simultaneously variables of internal control, human resource competence, and understanding of good governance have an influence on the performance of local governments. Partially, internal control affects the government's financial performance. And partially the variable of human resource competence has an effect on the performance of local government. Good governance partially has an influence on local government performance.Keywords: internal control, human resource competence, good governance, local government performance.